The Role of the House of Representatives in Guarding Government Policies to Resolve the Covid-19 Pandemic - Bayu Dwi Anggono; Fahmi Ramadhan Firdaus (Fiat Justisia: Jurnal Ilmu Hukum, 2021)
The responsibility to handle the Covid-19 Pandemic is not only carried out by the President as the highest leader of the government, but also the House of Representatives which holds the legislative branch of power, so far the public has questioned the seriousness of Parliament in handle the Pandemic, through its functions should be able to assist and especially to monitoring policy government to work together to handle this pandemic and as an effort to prevent potential abuse of power. The writing of this article uses the Juridical Normative method which will produce recommendations on how the House of Representatives should optimize its function during the Covid-19 Pandemic.